A simple and rapid screening method for grain zinc content in pearl millet - Velu, Govindan; Bhattacharjee, Ranjana; Rai, Kedar N.; Sahrawat, K.L.; Longvah, T. (2008)
Field and laboratory studies were conducted in Andhra Pradesh, India, to evaluate the effectiveness of a rapid screening method using Perl's Prussian blue stain for screening grain samples from different pearl millet genotypes for zinc (Zn) content. A total of 29 entries representing a wide range of grain Zn concentrations was evaluated in 5 different seasons for genotype × environment interaction. The estimation of grain Zn content was done using the sib-mated grain samples from the 2005 rainy and 2006 summer seasons following the AAS method. Of these, 9 pearl millet genotypes with a wide range of grain Zn content were chosen to standardize the DTZ staining procedure. The procedure was further validated using the grain samples of the remaining 20 entries obtained from sib-mating. Results showed that whole grain flour of pearl millet genotypes with different Zn concentrations, when treated with DTZ stain, showed an increase in the intensity of red colour formation with increasing Zn concentration. The intensity of red colour varied in genotypes having low, medium and high grain Zn content. In genotypes having high Zn content, the red colour was more intense than in those having medium Zn content. The intensity of red colour was very less or none in genotypes having less than 37 mg Znkg. DTZ staining can therefore be useful at least in separating flour samples with Zn concentrations lower than 40 mgkg. These results suggested that DTZ staining was effective in separating genotypes with high and low Zn contents. The cost analysis of DTZ staining protocol showed that the chemical cost per sample was approximately US$ 0.75, which showed that this method was simple, rapid and inexpensive.